FIX&FOXY’s poetik, metode og organisering: Interview med Tue Biering, oktober 2021 og januar 2022 - Exe Christoffersen, Erik; Winkelhorn, Kathrine; Krøgholt, Ida (Peripeti, 2022)
FIX&FOXY’s poetik, metode og organisering. Interview with Biering by Christoffersen, Krøgholt and Winkelhorn. Biering tells about the principles and the theatre view that have been guiding for FIX&FOXY’s creative and theatrical strategies throughout the theatre’s work.